2007
DOI: 10.1007/s00535-007-2073-5
|View full text |Cite
|
Sign up to set email alerts
|

Nodular gastritis in Japanese young adults: endoscopic and histological observations

Abstract: Diffuse-type NG depended on sex, and antral nodularity seemed to change from the diffuse to the nondiffuse type in association with atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 24 publications
(33 reference statements)
2
50
0
1
Order By: Relevance
“…Nodular gastritis was the most frequent endoscopic finding in our subjects, as it was recognized in two-thirds of students with H. pylori infection. It is well known that nodular gastritis is the most common endoscopic finding in youth with H. pylori infection [15], and the nodular appearance is composed of lymph follicles due to H. pylori infection. Atrophic gastritis was observed in about half of the students with H. pylori infection in our study; however, the endoscopic degree was determined to be the closed type in all of them.…”
Section: Discussionmentioning
confidence: 99%
“…Nodular gastritis was the most frequent endoscopic finding in our subjects, as it was recognized in two-thirds of students with H. pylori infection. It is well known that nodular gastritis is the most common endoscopic finding in youth with H. pylori infection [15], and the nodular appearance is composed of lymph follicles due to H. pylori infection. Atrophic gastritis was observed in about half of the students with H. pylori infection in our study; however, the endoscopic degree was determined to be the closed type in all of them.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no definite consensus regarding the association between symptoms and endoscopic findings, a recent study reported that patients with nodular gastritis exhibited a clinical amelioration of symptoms after H. pylori eradication therapy, and this is correlated with the endoscopic resolution of nodularity [27]. Nodular gastritis is generally more common among younger patients with mild atrophic mucosa [28]. In this study, we observed better amelioration of symptoms after H. pylori eradication therapy in the younger age group than in the older age group.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic biopsy of NG shows lymphoid follicles and the infiltration of mononuclear cells by histopathological examination [5,6,8,9]. Since the discovery of Helicobacter pylori, several studies have shown nodular gastritis to be closely associated with H. pylori infection [3,7,10,11].…”
Section: Introductionmentioning
confidence: 99%